2021
DOI: 10.1038/s41598-021-94939-2
|View full text |Cite
|
Sign up to set email alerts
|

Confocal spectral microscopy, a non-destructive approach to follow contamination and biofilm formation of mCherry Staphylococcus aureus on solid surfaces

Abstract: Methods to test the safety of wood material for hygienically sensitive places are indirect, destructive and limited to incomplete microbial recovery via swabbing, brushing and elution-based techniques. Therefore, we chose mCherry Staphylococcus aureus as a model bacterium for solid and porous surface contamination. Confocal spectral laser microscope (CSLM) was employed to characterize and use the autofluorescence of Sessile oak (Quercus petraea), Douglas fir (Pseudotsuga menziesii) and poplar (Populus eurameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In fact, we can make the hypothesis of low levels of these extracts in the wood samples tested here, which would impact the antibacterial properties. Another studies show the antibacterial properties of oak compared to other materials, including stainless steel, on four bacteria, two of which were identical to those used in our study 8 and a significantly greater decrease in Staphylococcus aureus colonisation over time on Douglas fir compared to oak and poplar 9 . So, it can be said the antibacterial properties of wood are timber-specific (Douglas fir, oak versus maritime pine), showing that the antibacterial action of certain species is not only due to the mechanical properties of the wood, but also to its molecular composition, its pH level, as several studies have shown 5 , 27 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In fact, we can make the hypothesis of low levels of these extracts in the wood samples tested here, which would impact the antibacterial properties. Another studies show the antibacterial properties of oak compared to other materials, including stainless steel, on four bacteria, two of which were identical to those used in our study 8 and a significantly greater decrease in Staphylococcus aureus colonisation over time on Douglas fir compared to oak and poplar 9 . So, it can be said the antibacterial properties of wood are timber-specific (Douglas fir, oak versus maritime pine), showing that the antibacterial action of certain species is not only due to the mechanical properties of the wood, but also to its molecular composition, its pH level, as several studies have shown 5 , 27 .…”
Section: Discussionsupporting
confidence: 74%
“…Douglas fir with an antibacterial coating showed no difference in bacterial survival compared to other materials, the coating can moderate the chemical and physical antibacterial activities of wood by affecting its surface structure, it can be said that this contributes to its lower effectiveness compared to raw Douglas fir versus stainless steel. In fact, several studies 9 , 28 , 29 show that the porosity of wood has an influence on its antibacterial properties, in particular by trapping bacteria deep down in an unsuitable environment for their survival. Similarly, Douglas fir shows a significant reduction in bacterial survival compared to pumice, a very porous material, which supports the fact that porosity plays a role in the antibacterial properties of wood, but is not the only one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations